The promised LAN: the transformative power of information and communications technology in developing countries - Booker, Lee Catherine (2013)
This thesis analyzes the prospects and implications of investment in Information and Communications Technology (ICT) in developing countries, particularly in terms of education, to spur the implementation of a more modern infrastructure versus conversion of traditional methods. Given the rapid pace of interest and investments in ICT, current readiness models and capability measurements have become outdated, inaccurate, and inapplicable to developing cultures. Policymakers and financiers must be cognizant of these considerations when evaluating investments in or aid for future ICT initiatives around the world, and researchers and educators should understand the factors involved in development for both ICTs and education before beginning studies in poor areas. This paper concludes that investments in mobile and wireless technologies will allow organizations and governments to leapfrog traditional infrastructure, narrowing the digital divide and resulting in enhanced education, higher literacy rates, and sustainable solutions for development in impoverished communities in the developing world.